Prevention of bladder cancer incidence and recurrence: tobacco use. Issue 1 (January 2018) - Soria, Francesco; Marra, Giancarlo; Čapoun, Otakar; Soukup, Viktor; Gontero, Paolo
Abstract : Purpose of review: To summarize the current knowledge about smoking carcinogenesis in bladder cancer (BCa), individual susceptibility and impact of smoking on incidence and outcomes of nonmuscle invasive BCa (NMIBC) and muscle-invasive BCa (MIBC). To assess the impact of smoking cessation on oncological outcomes. Recent findings: Smoking pattern, intensity, and duration are responsible for an increased risk of developing BCa and for worse tumor features at presentation. Tobacco consumption is associated with a higher risk of recurrence in NMIBC and with an impaired intravesical therapy efficacy. To date, the impact of smoking on oncological outcomes after radical surgery remains unclear. Summary: Smoking cessation decreases the risk of BCa and may also allow benefits on treatment outcomes. Nonetheless, the magnitude of the effect remains unclear and prospective series with the specific aim of weighing smoking cessation on outcomes are needed. Because even a 5-min counseling in the urology setting may be sufficient to significantly enhance smoking cessation rates, adequate knowledge of links between tobacco and BCa, from its molecular pathophysiology and its harms to benefits of cessation is paramount for urologists and for everyday clinical practice.